Magnetically controlled capsule endoscopy as the first-line examination for high-risk patients for the standard gastroscopy: a preliminary study. (3rd July 2019) - Hu, Jinlong; Wang, Shupeng; Ma, Wenzhuang; Pan, Duo; Sun, Siyu
Abstract: Background: Magnetically controlled capsule endoscopy (MCE) has emerged as a feasible and efficient diagnostic modality for gastric diseases. In a special group of patients, MCE may have an advantage over standard gastroscopy. Objective: This study aimed to evaluate the clinical utility of MCE in high-risk patients for standard gastroscopy. Methods: In this study, patients with high-risk factors for standard gastroscopy were examined by MCE between 1 January 2017 and 31 December 2017. The examination time, results, adverse events and clinical outcome were recorded. Results: Forty-two patients with high-risk factors for standard gastroscopy were enrolled in the present study. All patients successfully underwent MCE without any adverse events. Based on the findings from MCE, the patients were successfully treated. Conclusions: For patients with high-risk factors for standard gastroscopy, MCE could be the perfect alternative examination for gastric diseases. We recommend MCE as the first-line examination for high-risk patients, but its utility should be confirmed in further clinical studies.